Development of porous nickel catalysts by low-temperature Ni–Al chemical alloying and post selective Al leaching, and their application for ammonia decomposition. (31st July 2020) - Lee, Yu-Jin; Lee, Yong-Seok; Cha, Jun Young; Jo, Young Suk; Jeong, Hyangsoo; Sohn, Hyuntae; Yoon, Chang Won; Kim, Yongmin; Kim, Kwang-Bum; Nam, Suk Woo
Abstract: Micron-sized Ni–Al alloy powders (Ni– x wt.%Al, x = 40, 50, 60) were synthesized using the low-temperature chemical alloying (LTCA) at 500 °C. The three different as-prepared Ni–Al alloy powders were composed of Ni2 Al3 and/or NiAl3 phases while achieving thermodynamic equilibrium compositions (Ni–40 wt%Al, Ni2 Al3 ; Ni–50 wt%Al, the coexistence of Ni2 Al3 and NiAl3 ; Ni–60 wt%Al, NiAl3 ). The LTCA method demonstrates that it is capable of producing Al-rich Ni–Al alloy powders while maintaining a particle size similar to that of the starting Ni particles. The three Ni–Al alloy powders were used as precursor materials to fabricate porous nickel catalysts through a selective aluminum leaching process, followed by the enlargement of the surface area. Alteration of the material characteristics with respect to the leaching time was investigated using XRD, FESEM-EDS, TEM, XPS, TPR, BET, and particle size analysis. The nickel skeletal catalysts with the increased BET-surface areas (50–111 m 2 /g) displayed high reactivity toward ammonia decomposition. Graphical abstract: Image 1 Highlights: Ni–Al alloy powders were synthesized by a low-temperature chemical alloying method. Post aluminum leaching converts Ni–Al alloy precursors into porous nickel catalysts. Ammonia decomposition was successfully carried out using porous nickel catalysts.